Juegos tradicionales y motricidad gruesa en niños de 4 a 5 años, escuela de Educación Básica Alonso de Mercadillo, ciudad de Loja, periodo 2023-2024 - Calero Mendoza, Maria Belen (2024)
Gross motor skills are the ability to perform large and coordinated movements with the whole body. This development begins in early childhood and continues into adulthood. Developing gross motor skills is important for the physical, social, and emotional well-being of children as it allows them to explore their environment, participate in daily physical activities, have fun, and play with other children. Therefore, this study focused on determining how traditional games help improve gross motor skills in children aged 4 to 5 years at Alonso de Mercadillo Elementary School in Loja city, school year 2023-2024. A mixed-methods approach was used, allowing for both qualitative and quantitative analysis and data collection. A quasi-experimental design was employed, enabling the manipulation of the independent variable, traditional games. The analytical-synthetic methods allowed for the individual analysis of variables, collecting the most relevant information for the theoretical framework, and the inductive method led to the general conclusions of the research. The Ozzer Motor Neurological Evaluation Maturity Scale, created by Ozeretski (1929-1936), was used as an instrument to assess the level of gross motor coordination and balance of the children, showing that 41% were within the parameters of disability and loss of movements. After applying the activity guide called "The Magical World of Games," it was found that 92% of the children achieved the levels of correct and slight loss of movements. Therefore, the feasibility of implementing traditional games as a didactic strategy in the development of gross motor skills is corroborated, allowing children to strengthen their coordination and balance in a fun and appropriate way. Keywords: Motor coordination, motor skills, traditional games, physical well-being.